EFFECT OF CORPORATE SOCIAL RESPONSIBILITY ON INVESTMENT EFFICIENCY OF QUOTED OIL AND GAS FIRMS IN NIGERIA - Ibrahim, K.F.A.; Sylvester Onyekachi, Ademu (International Journal of Research -GRANTHAALAYAH, 2021)
This study examined effect of corporate social responsibility (CSR) on investment efficiency of quoted oil and gas firms in Nigeria. The study employed Ex post facto research design. The sample size of seven (7) oil and gas firms was derived from the population of the quoted twelve (12) oil and gas firms in Nigeria. Judgmental approach was employed during the sampling procedure. The study used secondary data sourced from the annual reports of the quoted oil and gas firms in Nigeria Stock Exchange fact books of official lists covering a ten-year period (2010-2019). The study employed Multiple Regression Model as the technique of data analysis with the aid of SPSS 23 statistical software. Analysis of findings showed that CSR charitable donation expenditure, CSR expenditure on education and CSR societal expenditure reveal significant relationship with investment efficiency of oil and gas firms in Nigeria. Nevertheless, CSR health expenditure and CSR environmental expenditure show insignificant effect on investment efficiency of oil and gas firms in Nigeria. The study also reveals that there is significant relationship between CSR sports expenditure and investment efficiency of oil and gas firms in Nigeria. With respect to the findings, the study recommends that the oil and gas firms should boost and monitor their CSR charitable donation expenditure, CSR on health expenditures, CSR environmental and CSR sport expenditures and observe them closely since they reveal negative effect. The study also recommends that CSR expenditure on education and CSR societal expenditure should be upheld and sustained since they reveal significant positive effect on investment efficiency of oil and gas firms in Nigeria.